Modeling extinction - Newman, M. E. J. (Mark E. J.); Palmer, Richard G. (Proceedings volume in the Santa Fe Institute studies in the sciences of complexity., 2003)
"In the last decade, scientists have taken a new approach to the patterns of evolution and extinction in the fossil record. Patterns like the distribution of the sizes of mass exinction events over time, the distribution of species lifetimes, or the apparent increase in the number of species alive over the last half a billion years are being reexamined to shed new light on extinction. Traditional studies of extinction have tended to adopt quite a narrow focus, but in attempting to model these patterns, researchers have drawn on ideas not only from paleontology but from evolutionary biology, ecology, physics, and applied mathematics, including fitness landscapes, competitve exclusion, interaction matrices, and self-organized criticality. Modeling Extinction presents a self-contained review of work in this field, including a summary of the important features of the fossil record and detailed discussions of many of the models of extinction which have been proposed."--Jacket.